Electrolyte disturbances after bowel preparation for colonoscopy: Systematic review and meta‐analysis. Issue 5 (23rd February 2022) - Reumkens, Ankie; van der Zander, Quirine; Winkens, Bjorn; Bogie, Roel; Bakker, Christine Minke; Sanduleanu, Silvia; Masclee, Ad A. M.
Abstract : Background and study aims: We conducted a systematic review and meta‐analysis of population‐based studies to explore pooled prevalence and magnitude of electrolyte changes after bowel preparation for colonoscopy based on the most recent guidelines. Patients and methods: PubMed and Cochrane were queried for population‐based studies examining changes in electrolyte values after bowel preparation, published by July 1, 2021. We report prevalences of serum hypokalemia, hyponatremia, hyperphosphatemia, and hypocalcemia after bowel preparation and changes in mean electrolyte values after vs. before bowel preparation using sodium phosphate (NaP) and polyethylene glycol (PEG). Results: Thirteen studies met the inclusion criteria; 2386 unique patients were included. Overall, hypokalemia was found in 17.2% (95% CI 6.7, 30.9) in the NaP group vs. 4.8% (95% CI 0.27, 13.02) in the PEG group. The magnitude of potassium decrease after NaP bowel preparation was significantly increased compared to PEG (mean difference −0.38; 95% CI −0.49 to −0.27, P < 0.001). No study reported on major complications. Conclusions: Hypokalemia was found in 17.2% of patients after bowel preparation with NaP and in 4.8% of patients with PEG, a finding that is clinically relevant with respect to choosing the type of bowel preparation. The magnitude of the potassium decrease after NaP was significantly higher compared to PEG. These data provide the evidence that supports the recommendation of the European Society of Gastrointestinal Endoscopy against routine use of NaP for bowel preparation.